REKONSTRUKSI PENDIDIKAN ISLAM DI ERA DISRUPSI: ANALISIS KARAKTERISTIK, SIKAP, DAN POLA PIKIR GEN Z TERHADAP PEMBENTUKAN AKHLAKUL KARIMAH - Budi Sarjana,; Fatikhatun Nikmatus Sholihah,; Ospa Pea Yuanita Meishanti, (Rihlah Review: Jurnal Pendidikan Islam, 2026)
This study explores the characteristics, attitudes, and mindsets of Generation Z (Gen Z) within the context of Islamic Religious Education (IRE) in the era of digital disruption. The phenomenon of shifting religious authority and the prevalence of mental health issues present new challenges to the relevance of IRE learning. Utilizing a qualitative method with literature review and netnographic approaches, this research finds that Gen Z tends to validate religious teachings rationally and is more responsive to love-based religious narratives rather than fear-based ones. The results indicate that a disconnection between rigid rote-learning materials and students' existential needs triggers dissatisfaction with conventional IRE methods. The study concludes by recommending a reconstruction of the IRE curriculum that integrates digital literacy, eco-theology, and mental health support to foster adaptive individual and social piety for Generation Z.